2022
DOI: 10.7759/cureus.32399
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparative Study of Long-Term Outcomes Following Cervical Total Disc Replacement Versus Anterior Cervical Discectomy and Fusion

Abstract: IntroductionThe traditional treatment for patients with radiculopathy and myelopathy caused by degenerative disc disease was anterior cervical discectomy and fusion (ACDF). However, a documented complication of ACDF is adjacent segment degeneration (ASD). An alternative that was developed was total disc replacement (TDR).The aim of this study was to determine and compare the short-and medium-to-long-term outcomes after a TDR or ACDF. MethodsA retrospective review of 154 patients who had single and two-level AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…ACDF is standard treatment method when the conservative treatment of SCIWFD fails. Niu et al [6] concluded that patients undergoing ACDF in combination with a PEEK interbody spacer and anterior xation had a high rate of fusion success, for the fusion rates were reported to be unacceptably low after multi-level ACDF without plating [7,8] . However, the use of additional plate is associated with various complications, including increased risks of hardware failure and postoperative dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…ACDF is standard treatment method when the conservative treatment of SCIWFD fails. Niu et al [6] concluded that patients undergoing ACDF in combination with a PEEK interbody spacer and anterior xation had a high rate of fusion success, for the fusion rates were reported to be unacceptably low after multi-level ACDF without plating [7,8] . However, the use of additional plate is associated with various complications, including increased risks of hardware failure and postoperative dysphagia.…”
Section: Discussionmentioning
confidence: 99%